Malathion-Induced Oxidative Stress, Cytotoxicity and Genotoxicity in Human Liver Carcinoma (HepG(2)) Cells - Moore, Pamela D. (2010)
Malathion is an organophosphate pesticide that is known for its high toxicity to insects and low to moderate potency to humans and other mammals. Its toxicity has been associated with the inhibition of acetylcholinesterase activity, leading to the interference with the transmission of nerve impulse, accumulation of acetylcholine at synaptic junctions, and subsequent induction of adverse health effects including headache, dizziness, nausea, vomiting, bradycardia, and miosis. Oxidative stress (OS) has been reported as a possible mechanism of malathion toxicity in humans. Hence, the aim of the present study was to examine the role of OS in malathion-induced cytotoxicity and genotoxicity. To achieve this goal, MTT, lipid peroxidation, and single cell gel electrophoresis (Comet) assays were performed, respectively to evaluate the levels of cell viability, malondialdehyde (MDA) production, and DNA damage in human liver carcinoma (HepG(2)) cells. Study results indicated that malathion is mitogenic at lower levels of exposure, and cytotoxic at higher levels of exposure. Upon 48 h of exposure, the average percentages of cell viability were 100±11%, 117±15%, 86±15%, 35±9%, and 27±7% for 0, 6, 12, 18, and 24 mM, respectively. In the lipid peroxidation assay, the concentrations of MDA produced were 12.55±0.16, 20.65±0.27, 31.1±0.40, 34.75±0.45, and 15.1±0.20 μM in 0, 6, 12, 18, and 24 mM of malathion, respectively. The Comet assay showed a significant increase in DNA damage at the 24mM malathion exposure. Taken together, our results indicate that malathion exposure at higher concentrations induces cytotoxic and genotoxic effects in HepG(2) cells, and its toxicity may be mediated through oxidative stress as evidenced by a significant production of MDA, an end product of lipid peroxidation.